Agonistic democracy and the challenges of diversity: exploring practical applications of conflict mediation - Paxton, Marie (2015)
This research explores whether, and how, theoretical concepts from agonistic democracy could be operationalised in order to mediate conflict in multicultural, pluralist society. It highlights three central themes of agonistic democracy: political contestation, contingency and necessary interdependency. It subsequently demonstrates the various ways in which these themes are employed, delineating three distinct agonistic approaches: the ‘perfectionist’ (as encapsulated by David Owen), the ‘adversarial’ (as represented by Chantal Mouffe), and the ‘inclusive’ (as symbolised by William Connolly and James Tully). The research then considers possible tensions between agonistic assumptions and further institutional consideration, and draws on new institutionalist literature to identify which kinds of institution could be compatible with agonistic democracy. It explores these through an experiment, which employs three distinct discussion frameworks, each representing a different agonistic approach. The research combines insights from the experiment and agonistic literature to gain a deeper insight into agonistic concepts and the potential for their operationalisation. It suggests that perfectionism is valuable in encouraging unity, adversarialism is effective in reviving passions, and inclusivity is useful in enhancing interactions between conflicting citizens. Finally, the research proposes an ‘agonistic day’ and demonstrates how a synthesis of all three approaches could mediate multicultural, pluralist conflict.